Legal Analysis of the Merah Putih Village Cooperative in Patak Banteng Village Based on Indonesian Cooperative Law - Atok Safik Takiyapudin; Sri Jumini; Adi Suwondo; Mutho'am; Nila Amania (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2026)
The Merah Putih Village Cooperative is a government initiative aimed at strengthening village-based economic institutions and promoting community welfare. This study examines the conformity of the establishment and implementation of the Merah Putih Cooperative in Patak Banteng Village with Law Number 25 of 1992 concerning Cooperatives. The research employed a qualitative descriptive method using statutory and empirical approaches through the analysis of legal documents, government regulations, field observations, and interviews. The findings indicate that the establishment process has complied with the legal framework stipulated in Law Number 25 of 1992, Presidential Instruction Number 9 of 2025, and Circular Letter Number 1 of 2025. The cooperative has fulfilled essential legal requirements regarding membership, organizational structure, and legal entity formation. However, challenges remain in strengthening managerial capacity, legal literacy, and institutional governance. The study highlights that transparency and effective supervision are crucial to ensuring accountability and legal compliance in cooperative management. Therefore, continuous legal assistance, capacity-building programs for cooperative managers, and the implementation of transparent monitoring mechanisms are recommended to support the sustainability and effectiveness of the Merah Putih Cooperative as an instrument for village economic development.